Navigating Archipelagic Fisheries Through An Optimization Strategy For Fisheries Port Utilization To Support The Sustainable Tuna, Skipjack, And Tongkol (Tct) Fisheries Industry In Ntt Province, Indonesia - Welhelmina L. Kause; Marince P. Tunardjo; Noverius H. Nggili; Aprianus R. P. Modena; Dalmasius Naif; Adellia Agusta; Roidah ‘Afro’; Descorina P. Br. Sitompul; Yohanes Frenky; Lisa Novalia (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
Despite the considerable potential of the tuna, skipjack, and tongkol (TCT) fisheries in East Nusa Tenggara (NTT) Province, their economic contribution remains stagnant due to the underutilization of port facilities. This study evaluates the utilization of fishing port facilities at PPI Oeba and PPP Tenau in Kupang City, identifies operational constraints, and formulates strategic optimization plans for the long-term development of the TCT fisheries industry. A mixed-methods approach was employed, integrating quantitative surveys from 180 respondents comprising fishermen, logistics providers, processing entrepreneurs, and port managers with qualitative in-depth interviews with key stakeholders. Stakeholder perceptions were assessed using a five-point Likert scale and the instrument was subjected to validity and reliability testing prior to full deployment. Findings reveal that while primary facilities at PPI Oeba are relatively functional (mean score: 4.03), PPP Tenau faces critical challenges arising from infrastructure aging dating to 1977 and severely limited operational capacity relative to current TCT industry demand. Key obstacles identified include non-functional cold chain systems, weak institutional governance, inadequate waste management, and low stakeholder participation in policy-making. Strategic recommendations encompass infrastructure revitalization, institutional governance reform, digitalization through GIS-based monitoring, investment facilitation, and implementation of the Eco-Fishing Port concept. This study underscores the imperative of transforming fishing ports from passive landing sites into integrated maritime–industrial hubs to enhance the regional value chain and ensure long-term sustainability of archipelagic fisheries.